'Why is it so different now I'm bisexual?': young bisexual people's experiences of identity, belonging, self-injury, and COVID19. Issue 3 (3rd July 2022) - Dunlop, Brendan J; Hunter, Cheryl; Shafti, Matina; Coleman, Sophie E; Hartley, Samantha; Taylor, Peter J
ABSTRACT: Bisexual people demonstrate higher rates of Non-Suicidal Self-Injury (NSSI) in comparison to other groups. This study aimed to explore bisexual people's experiences of sexuality, NSSI and the COVID19 pandemic. Fifteen bisexual people (16–25 years old) with experience of NSSI participated in online qualitative interviews. Thematic analysis was used. Preliminary findings were shared with a subset of participants for member-checking. Participants described experiences of falling between the binary worlds of heterosexuality and homosexuality and described discrimination and invalidation related to this. Lack of access to positive bisexual representation contributed to feelings of self-loathing, with NSSI used to manage emotions or self-punish. The effect of lockdown was not clear cut, depending on personal circumstances and meanings of social interaction for participants. There is a need for greater recognition of significant societal narratives around bisexuality within clinical formulations of mental health difficulties and NSSI within this population.